From pedagogy to quality assurance in education : an international perspective - Flavian, Heidi, 1965- (Emerald Publishing Limited, 2020)
In an increasingly global world, it is more important than ever that educators are equipped to respond to the needs of international student cohorts. This book is a fruitful resource for researchers, educators, and others, who wish to develop new approaches and educational models to contribute to the efficient process of learning.